Studi Korelasi Antara Personal Branding Owner Tasya Farasya Dan Kualitas Produk Terhadap Keputusan Pembelian Brand Makeup Mother Of Pearl - Hanifah, Addiena; Sudrajat, Ajat (Politeknik Negeri Ambon, 2024)
Tasya Farasya is a beauty influencer who is being talked about. She often reviews beauty products on social media such as Instagram and TikTok. Through her experience and knowledge in the beauty world, she is able to easily influence her followers to buy the products she recommends. This study aims to answer whether personal branding and product quality have a relationship with purchasing decisions. The research involved one hundred participants who were asked to fill out a questionnaire in a quantitative study. Based on the findings of this study, Tasya Farasya's personal branding and product quality are two factors that significantly influence consumer purchasing decisions. Keywords: Tasya Farasya; Personal Branding; Product Quality; Buying decision